Excision and suture in the midline versus Karydakis flap surgery for pilonidal sinus: randomized clinical trial. Issue 2 (15th March 2022) - Hemmingsson, Oskar; Binnermark, Felix; Odensten, Christoffer; Rutegård, Martin; Franklin, Karl A.; Haapamäki, Markku M.
Abstract: Background: There are several surgical options for the management of pilonidal disease, including midline and off midline closure, but prospective studies are rare. The study hypothesis was that Karydakis flap surgery would result in shorter wound healing and fewer recurrences than excision of pilonidal sinus and suture in the midline. Methods: A randomized clinical trial was conducted in two hospitals in Sweden between 2006 and 2015 to compare excision and suture in the midline with Karydakis flap surgery. Adult patients with a chronic pilonidal sinus disease were randomized 1:1 at the outpatient clinic without blinding. Power calculation based on recurrence of 2 per cent for Karydakis flap and 10 per cent for excision and primary closure in the midline required 400 patients with 90 per cent statistical power at 5 per cent significance assuming 10 per cent loss during follow-up. Participants were followed up until complete wound healing; late follow-up after 6–13 years was performed by telephone by two blinded assessors. The two co-primary outcomes were time to complete wound healing and recurrence rate. Results: The study was terminated early at a planned interim analysis due slow recruitment and a significant difference in primary outcome. In total, 125 patients were randomized, of whom 116 were available for the present analysis. Median wound healing time was 49 days (95 per cent confidence interval (c.i.) 32 to 66) for excision with suture in the midline and 14 days (95 per cent c.i. 12 to 20) for Karydakis flap surgery ( P  < 0.001). There were five recurrences in each group, after a median follow-up of 11 years ( P  = 0.753). Conclusion: Karydakis flap surgery for pilonidal sinus disease led to a shorter wound healing time than excision and suture in the midline but no difference in recurrence rates. Registration number: NCT00412659 (http://www.clinicaltrials.gov ) Abstract : Two surgical techniques for pilonidal sinus disease were studied in an expertise-based randomized controlled trial with long term follow-up. Karydakis flap surgery for pilonidal sinus disease leads to a shorter wound healing time than excision and suture in the midline, while the recurrence rate is similar.